Sensitivity of personalized ventilation air terminal device geometry with regard to a human thermal sensation. (3rd October 2017) - Bogdan, Anna; Chludzińska, Marta; Koelblen, Barbara; Ogłodzinski, Kacper; Młynarczyk, Magdalena
Abstract : Thermal comfort of people using personalized ventilation system is affected by the amount of air and the air terminal devices. However impact of small changes in air terminal device's geometry alone has not been examined and assessed. The aim of the current article was to compare thermal sensations and productivity of users who used three kinds of personalized ventilation air terminal devices with similar construction (the same size of a box, the same perforated surface used inside) and differs in spacing of blinds used at the outlet of the device. During the measurement volunteers were asked to complete a questionnaire survey containing questions about: local and general thermal comfort, air movement, expectations for thermal environment, dryness of the eye, and their mood and fatigue. Statistical analysis were conducted to examine whether significant differences in volunteers responses among air terminal devices occur. The results showed the significance of the geometry and design of air terminal device on user' thermal sensations. Changes in the perception of thermal environment were mostly felt after 2 and 3 h of exposure to the microenvironment shaped by personalized ventilation. The changes concerned mainly the perception of thermal environment, which also translated into respondents' self-assessment and, in the long-term, into their productivity.